Analisis Produksi dalam Perspektif Ekonomi Islam (Studi Kasus UD H. Nur Desa Potoan Daja) - Zainol Fata; Paesol (Alkasb: Journal of Islamic Economics, 2022)
Production is an activity carried out by humans in order to meet basic needs in their lives. UD H. Nur is one of the businesses in Potoan Daja Village, Palengaan Pamekasan. The business activities carried out are processing raw materials such as wood in the process into products that have a higher value and a different benefit value after being produced. The purpose of this paper is to determine the implementation of UD H. Nur's production factors in Potoan Daja Village, Palengaan, Pamekasan and to determine the implementation of UD H. Nur's production factors in Potoan Daja Village, Palengaan, Pamekasan in an Islamic economic perspective. This research is included in the qualitative research. The approach used in this research is a descriptive approach. Data and data sources in this study are divided into two, namely primary data and secondary data. Techniques in collecting data authors use three ways, namely by observing, interviewing and documentation. After conducting research, it can be understood that the implementation of UD H.Nur's industrial production factors in Potoan Daja Village, Palengaan, Pamekasan, namely natural factors, labor factors, capital factors, technological factors and entrepreneurial or management factors. While the implementation of UD H. Nur's industrial production factors in Potoan Daja Village, Palengaan, Pamekasan in an Islamic economic perspective, namely land factors (natural resources), natural resources, capital and organizational or management factors